Toward a Sociological Theory of Labour Relations - Garry, Carl (Canadian Journal of Higher Education, 1978)
During the 1970's unionization among professional employees in Canada has increased and this trend has been evident among university faculty members. The case study of unionization of faculty at "Eastview University" shows that the literature of voluntary associations and consideration of the historical, political and economic environment of unionization is relevant to the study of unionization in Canada. The literature of labour relations has emphasized economic considerations and been dominated by practitioners. The case study shows that the university's faculty association was an expressive type of voluntary association. Changes in the university's environment led to increased pressures on faculty members and they experienced a sense of powerlessness. The faculty association became a faculty union, an instrumental association. Both faculty association and faculty union performed functions common to voluntary associations, conferring status and integrating the group. Economic factors were not the major factors for unionization at Eastview and the socio-psychological factors of insecurity and lack of full status as professionals were more influential. Further consideration of socio-psychological factors, following the model given in the article, will lead to fuller understanding of unionization and the role of professionals in bureaucracies.